'You have to work from where they are': academic leaders' talk about language development. Issue 1 (2nd January 2020) - Nicholls, Karen
ABSTRACT: Language development is integral to learning, teaching and assessment. In higher education language is usually only discussed when it becomes visible through errors or unexpected uses. Occasionally, national or institutional policies support the fundamental role of language development. More often, language development provision is sporadic. Despite academic leaders' role as key stakeholders in institution-wide language development strategies, their conceptualisations of language development have rarely been subject to in-depth study. This qualitative case study investigates academic leaders' understandings of language development in higher education, both students' and their own. An inductive thematic analysis of the data reveals three significant themes relating to language, learning and context. The contribution of this article is the analysis of inconsistencies and contradictions within those themes through the lens of language as a social semiotic. The analysis highlights how students' language development opportunities can be limited by institutional practices and raises policy implications for higher education.